PENGARUH TOTAL ASSET TURNOVER, CURRENT LIABILITIES TO INVENTORY, GROSS PROFIT MARGIN TERHADAP PERTUMBUHAN LABA - Ayuanti, Rafikhein Novia; E, Nadya Amailia (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 2 No 01 (2022): Januari-Mei 2022, 2022)
The research objective is to analyze the ratio of Total Asset Turnover, Current Liability to Inventory, Gross Profit Margin on the profit growth of PT Indofood CBP Tbk for the period 2013-2020. The type of this research is quantitative with a descriptive approach. The research sample is 32 financial statements from quarters 1 to 4 PT. Indofood CPB Tbk period 2013 - 2020. The analysis technique used is multiple linear regression. The results showed that based on the results of the partial t test, Total Asset Turnover and Current Liability to Inventory had no significant effect on profit growth, while Gross Profit Margin had a positive and significant effect on profit growth. Furthermore, the results of the f statistic test show that the variables of Total Asset Turnover, Current Liability to Inventory, Gross Profit Margin simultaneously have a significant effect on profit growth